Politics and Religion in the Perspective of Christian Philosophy of Father Hieronim Kajsiewicz CR - Mikucki, Kazimierz (Filozofia Chrześcijańska, 2024)
The article presents philosophical and theological views of Rev. Hieronim Kajsiewicz on the relationship between politics and religion from Christian philosophy perspective. As a supporter of their autonomy, he also advocated their cooperation for the broadly understood good of man. He justified their autonomy on the basis of their diﬀerent nature, thus revealing the truth of human existence, which is realized as if in the sphere of two diﬀerent stages, worlds and goals. He explained the necessity of cooperation between both on the ground of truth of God’s relation to man and creation and on the ground of the existential situation of a believer in this world. In practice, this dealt with basic forms of social life, especially with the nation.